4-Hexylresorcinol Loaded Solid Lipid Nanoparticles for Enhancing Anticancer Activity - Sooho Yeo; Sukkyun Jung; Haneul Kim; Jun-Hyun Ahn; Sung-Joo Hwang (MDPI AG, 2024)
Background: Cancer is one of the most significant threats to human health. Following surgical excision, chemotherapy is an effective strategy against remaining cancer cells. 4-hexylresorcinol (4-HR) has anti-cancer properties and exhibits hydrophobicity-induced aggregation in the blood that has trouble with targeted tumor delivery and cellular uptake of the drug. The purpose of this study is to encapsulate 4-HR into solid lipid nanoparticles (SLNs) to enhance its anti-cancer effect by avoiding aggregation and facilitating cellular uptake. Methods: 4-HR SLNs were prepared via hot melt homogenization with sonication. SLN characteristics were assessed by analyzing particle size, zeta potential, and drug release. Cytotoxicity, as an indicator of the anti-cancer effect, was evaluated against HeLa (cervical cancer in humans), A549 (lung cancer in humans), and CT-26 (colon carcinoma in mice) cell lines. Results: Particle size ranged from 169.4 to 644.8 nm, and zeta potential ranged from −19.8 to −40.3 mV, which are conducive to cellular uptake. Entrapment efficiency (EE) of 4-HR was found to be 75.0-96.5%. The cytotoxicity of 4-HR-loaded SLNs demonstrated enhanced anti-cancer effects compared to pure 4-HR. The enhancement of anti-cancer effects depended on reduced particle size based on cellular uptake, the EE, and the cell type. Conclusions: These findings imply that 4-HR-loaded SLN is a promising strategy for chemotherapy in cancer treatment.